2020
DOI: 10.3390/brainsci10070456
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Detects Pattern of Differences in Functional Magnetic Resonance Imaging (fMRI) Data between Chronic Fatigue Syndrome (CFS) and Gulf War Illness (GWI)

Abstract: Background: Gulf War Illness (GWI) and Chronic Fatigue Syndrome (CFS) are two debilitating disorders that share similar symptoms of chronic pain, fatigue, and exertional exhaustion after exercise. Many physicians continue to believe that both are psychosomatic disorders and to date no underlying etiology has been discovered. As such, uncovering objective biomarkers is important to lend credibility to criteria for diagnosis and to help differentiate the two disorders. Methods: We assessed cognitive differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
(73 reference statements)
0
15
0
Order By: Relevance
“…The STOPP – START dichotomy in GWI was associated with differences in postexercise cerebrospinal fluid glutamate ( Fig 1 ), miRNA [ 26 ] and differential activation of cerebellar and other brain regions by fMRI [ 31 33 ]. This dichotomy does not appear to be as influential in ME/CFS or control subsets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The STOPP – START dichotomy in GWI was associated with differences in postexercise cerebrospinal fluid glutamate ( Fig 1 ), miRNA [ 26 ] and differential activation of cerebellar and other brain regions by fMRI [ 31 33 ]. This dichotomy does not appear to be as influential in ME/CFS or control subsets.…”
Section: Discussionmentioning
confidence: 99%
“…First, “nonexercise” subjects rested overnight before history and physical, phlebotomy and lumbar puncture (nonexercise groups abbreviated as sc0 , cfs0 and gwi0 ) [ 26 ]. Second, a model of exertional exhaustion was developed by having subjects perform submaximal bicycle exercise on 2 consecutive days with functional magnetic resonance imaging (fMRI) studies performed at baseline and after the stress tests [ 27 33 ]. Lumbar puncture was performed after the post-exercise MRI in sedentary control ( SC ) and GWI subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ML algorithms have been applied to study a wide range of neurological disorders, including Alzheimer’s disease, Parkinson’s disease, and traumatic brain injury [ 17 , 18 ]. These studies have reported promising results for identifying diagnostic biomarkers [ 19 , 20 ]. The ML approach have strengths on exploiting features from different domains (i.e., neuropsychological, genetic and neuroimaging) and providing further insights on the potential interactions between different markers for classifying illness [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Brain activity and connectivity encapsulate important and complementary features related to human brain dynamics that can further feed a machine learning scheme. A novel study by Provenzano et al [ 7 ] attempts to identify the critical brain areas in which their brain pattern can differentiate subjects with Gulf War Illness (GWI) and chronic fatigue syndrome (CFS). Both disorders share similar symptomatology that involves fatigue, chronic pain, and exertional exhaustion after exercise.…”
mentioning
confidence: 99%